Color motivated PowerPoint presentation texts and Bioethics learning management (Atenas, 2021)
PowerPoint presentations are ubiquitous in contemporary education. Objective: To demonstrate the positive influence of motivated color texts of PowerPoint presentations in Bioethics learning. Method: Four Level V groups of 35 medicine students each, of the Manabí Technical University were included. Group A1 and A2 received classical black texts PowerPoint presentations during the first half and color texts presentations in the second half of the Bioethics course semester. Red and green colors were intentionally used according to the ethical value of the terms. Groups B1 and B2 presentations order was inverse, color texts during first have and black texts in the final half of the semester. Daily evaluation and final exam qualification scores with color texts presentations were compared to those with black texts. Results: Daily evaluations and exams scores were significantly better with the use of color motivated texts Bioethics presentations in all four groups. Conclusions: Learning results are positively affected by color motivated presentations texts in Bioethics teaching for medicine students.